Grand unification and proton stability near the Peccei-Quinn scale - Dias, A. G.; Pleitez, V (American Physical Soc, 2004)
We show that in an SU(2)circle timesU(1) model with a Dine-Fischler-Srednicki-like invisible axion it is possible to obtain (i) the convergence of the three gauge coupling constants at an energy scale near the Peccei-Quinn scale; (ii) the correct value for sin(2)theta<^>(W)(M-Z); (iii) the stabilization of the proton by the cyclic Z(13)circle timesZ(3) symmetries which also stabilize the axion as a solution to the strong CP problem. Concerning the convergence of the three coupling constants and the prediction of the weak mixing angle at the Z peak, this model is as good as the minimal supersymmetric standard model with mu(SUSY)=M-Z. We also consider the standard model with six and seven Higgs doublets. The main calculations were done in the 1-loop approximation but we briefly consider the 2-loop contributions.